Analisis Budaya dan Nilai-Nilai Organisasi (Studi Kasus PT Telkom Indonesia) - Fauzan Fajrullah; Adika Yuwanda; Fajar Wilandra Suntara; Randi Arista Pratama (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2025)
This study aims to analyze the organizational culture and values implemented by PT Telkom Indonesia, particularly within the context of the digital era that demands continuous transformation. As a state-owned enterprise operating in the information and communication technology sector, PT Telkom Indonesia has undergone an evolution of its organizational culture from The Telkom Way to The Telkom Way in Digital Era, reflecting the company’s strategic efforts to adapt to external changes and global demands. This culture comprises three main elements: Basic Belief (Always the Best), Core Values (Solid, Speed, Smart), and Key Behaviours (Imagine, Focus, Action), along with additional digital values encompassed in Telkom CODES, serving as guidelines for collaborative work behavior in the digital age. The research employs a qualitative method using a literature review approach. Data were collected from various literature sources such as scientific journals, company reports, news articles, and relevant official documents. The findings are presented descriptively and analytically, outlining how these cultural values are internalized and implemented by all Telkom employees as part of the organization's transformation strategy. The results indicate that the organizational culture change at Telkom is not merely symbolic but is aimed to have a tangible impact on work behavior, decision-making, and the achievement of corporate goals. A strong and adaptive organizational culture proves to be a crucial foundation for the company's sustainability and growth amid the challenges of digitalization. A deep understanding of the construction of organizational cultural values, as practiced by PT Telkom Indonesia, is highly relevant to serve as a model for other organizations undergoing similar transformations.